Practical Applications in Reliability Engineering - Zubair, Muhammad (IntechOpen, 2021)
This book compiles and examines advanced technologies in the field of reliability and risk analysis. It presents comprehensive methodologies and up-to-date software along with examples of practical case studies from industrial areas to provide a realistic and authentic platform for readers.